Design, synthesis and anti-diabetic activity of some novel xanthone derivatives targeting alpha-glucosidase - Bairy, Partha Sarathi; Das, Aparoop; Nainwal, Lalit Mohan; Mohanta, Tapan Kumar; Kumawat, Mukesh Kumar; Mohapatra, Pradyumna Kishore; Parida, Pratap (Bangladesh Journal of Pharmacology, 2016)
Twenty eight xanthone derivatives were designed and docked into the N-terminal catalytic domain of maltase-glucoamylase (ntMGAM) by considering Miglitol as standard drug. Most of the molecules showed excellent docking scores and docking interaction as compared to the binding cavity of the standard molecule. The five best scoring ligands were synthesized and characterized by a number of analytical and spectroscopic techniques. The molecules were screened for the in vivo antidiabetic activity in streptozotocin (STZ) induced diabetic animal model in Wistar rats. Compound P4 showed the most prominent inhibition among others. The synthesized compounds reported significant (p< 0.01) effect of lowering glucose levels in the blood compared to miglitol as a standard alpha-glucosidase inhibitor. Video Clips of Methodology: Synthesis of hydroxyxanthones: 7 min 2 sec Click to watch Induction of diabetes: 1 min 39 sec Click to watch